Intervention or Non-intervention, the Legalities of R2P and the Human Rights Agenda - Gabriel Bell (Politikon, 2017)
The threat of violence alongside the deep-rooted fear of falling into old patterns of animosity and violence have pushed the international community towards stringent controversial approaches regarding international conflicts. R2P initially started as a call on states to respect international policies pertaining to human rights within their own sovereign territories and to intervene when these rights are threatened. Currently, R2P has evoked controversial responses from the international community which have resulted in undesirable situations which include the violation of international law as well as the death of countless innocent civilians alongside public property. By researching the procedure behind intervention into numerous conflicts, as well as the legal aspect of intervention as an acceptable foreign policy, R2P as a response to conflicts will be scrutinized with the aims of arriving at a practical and response to the legalities of international intervention into conflicts.